1987
DOI: 10.1021/bi00382a042
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synthesis of 16S ribosomal RNA containing single base changes and assembly into a functional 30S ribosome

Abstract: Functional 30S ribosomes were reconstructed from total Escherichia coli 30S ribosomal proteins and 16S ribosomal RNA synthesized in vitro by T7 RNA polymerase. Up to 700 mol of RNA/mol of template could be obtained. The transcript lacked all ten normally modified bases and had three additional 5' G residues, an A----G change at position 2, and, in 22% of the molecules, one or two extra 3' residues. The synthetic 16S RNA could be assembled into a particle that cosedimented with authentic 30S and was indistingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
130
1
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 57 publications
5
130
1
2
Order By: Relevance
“…The possibility of ineffective ribosome assembly should be considered since Krzyzosiak et al (1987) noted that in vitrosynthesized G1400 containing rRNA is inefficient in the assembly process. However, another publication from the same group showed that such G1400 containing rRNA could be assembled efficiently provided that higher rRNA concentrations were used in the assembly reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of ineffective ribosome assembly should be considered since Krzyzosiak et al (1987) noted that in vitrosynthesized G1400 containing rRNA is inefficient in the assembly process. However, another publication from the same group showed that such G1400 containing rRNA could be assembled efficiently provided that higher rRNA concentrations were used in the assembly reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The overall scheme involves the assembly of a mutant ribosome pool in vivo, thus avoiding the inefficiency of in vitro reconstitution (22)(23)(24)(25)(26). The pool of variant ribosomes isolated from Escherichia coli is then subjected to selective pressure in vitro, where the definition of ''functional'' can be exquisitely manipulated.…”
mentioning
confidence: 99%
“…In rRNA, which next to tRNA contains the widest known assortment of modified nucleosides, no function has so far been ascribed to them, although a potential role in peptide bond formation for a subset of the modified nucleosides of Escherichia coli 23 S RNA has been postulated (3). In E. coli 16 S RNA, in which all of the modified nucleosides are known and their locations precisely determined, none was essential for any of the known ribosomal functions, although ribosomal efficiency was reduced to approximately half when all were absent (4,5). Evidence has been presented that this lowered efficiency of the 30 S subunits may be attributable to the lack of one or more of the 10 methylated residues and/or the single pseudouridine (6) in the RNA (7).…”
mentioning
confidence: 99%